Protagonistas na Sociedade Civil: Redes e Centralidades de Organizações Civis em São Paulo - Adrian Gurza Lavalle; Graziela Castello; Renata Mirandola Bichir (Universidade do Estado do Rio de Janeiro, 2007)
Using network analysis, this article identifies the main leading collective actors within civil society, and especially their different logics of performance and the dynamics of interaction amongst them. The findings of a survey of 202 civil organizations in the city of São Paulo showed that NGOs, coordinating bodies and social movements form the group of actors with the greatest capacity for action within the universe of civil organizations. Analyzed in a relational perspective, the three types of actors manifested themselves as the most central and characterized by an accumulation of structural advantages within the universe researched. The article shows that their centrality results from different factors, as well as that they fulfill different roles and differ in importance for other civil organizations which are peripheral or have an intermediate centrality in the network.